Pemanfaatan jagung (Zea mays) sebagai bahan tambahan dalam pembuatan permen Jelly - Raden Rizki Amalia; Ema Lestari; Nia Erika Safitri (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Candy is a snack that is loved by many people, especially children because it has a sweet taste. The texture of the candy is divided into hard candy (hard candy) and soft candy (soft candy). One example of soft candy is jelly candy. Jelly is a candy made from water or plant juice and gel-forming material. The material that can be used in making jelly candy is juice from corn. Corn is a cereal crop that contains starch or sugar, this corn is usually needed in the industrial world as feed or in the food processing industry. The purpose of this study was to produce corn jelly candy products favored by panelists through hedonic testing, hedonic quality, moisture content, ash content, and pH in accordance with SNI (Indonesian National Standard). This research method is experimental with the addition of corn juice in the manufacture of jelly candy with formulations of 0 grams, 90 grams, 100 grams, and 110 grams, then tested the level of preference (hedonic), hedonic quality, water content, ash content, and acidity. The results showed that the best formulation was 110 grams with hedonic values of color, texture, aroma, and flavor parameters which were highly favored by the panelists, hedonic quality values were very rubbery, the aroma was very flavorful typical of corn and the taste was very corny. Value of water content of 7.80%, ash content of 0.33%, and pH or acidity level 6.